Céline Dion et l'identité québécoise. « La petite fille de Charlemagne parmi les grands ! » - Demers, Frederic (VLB Éditeur, 1999)
Pourquoi Céline Dion est-elle une figure identitaire de premier plan aux yeux de la plupart des Québécois? Serait-ce parce qu'elle incarne l'équilibre qu'il recherchent désormais entre la préservation d'un héritage culturel particulier et l'ouverture à l'Autre sous le poids de la mondialisation et du métissage?

Inuit Throat-Games and Siberian Throat Singing: A Comparative, Historical, and Semiological Approach - Nattiez, Jean-Jacques (Ethnomusicology, 1999)

Céline Dion, the ADISQ Controversy, and the Anglophone Press in Canada - Young, David (Canadian Journal of Communication, 1999)
Abstract: ADISQ, the organization that honours excellence in the Quebec music industry, gave francophone singer Céline Dion an award for being the Anglophone Artist of the Year in 1990. At the ADISQ gala that year, which was televised live across Canada, Dion refused to accept the award. Dion's decision to not accept the award, and the statement she made when turning it down, became the basis for a controversy that received a great deal of coverage in Canada's anglophone press. This paper examines anglophone press coverage of the ADISQ controversy involving Dion. After outlining press coverage of Dion and ADISQ during the years prior to the controversy, the paper identifies how the controversy began and analyses the issues that dominated the coverage. The paper also examines follow-up coverage of the controversy; it identifies how subsequent news stories on Dion, including some that were written several years later, linked the controversy to other issues. Résumé: L'ADISQ, l'organisme qui reconnaît l'excellence dans l'industrie de la musique au Québec, accorda à la chanteuse francophone Céline Dion le prix du Meilleur Artiste anglophone de l'année 1990. Au gala de l'ADISQ cette année-là-qui fut télévisé en direct partout au Canada-Dion a refusé d'accepter le prix. Cette décision, ainsi que les commentaires que Dion a faites en refusant le prix, suscitèrent une controverse qui fit couler beaucoup d'encre dans la presse anglophone au Canada. Cet article examine comment la presse anglophone a couvert cette controverse de l'ADISQ impliquant Dion. Après avoir tracé les grandes lignes des reportages sur Dion et l'ADISQ dans les années précédant la controverse, cet article identifie comment la controverse commença et analyse les questions qui dominèrent dans la couverture de celle-ci. Cet article examine en outre la couverture suivant la controverse; il identifie comment des reportages ultérieurs sur Dion, y compris certains qui apparurent plusieurs années plus tard, associèrent la controverse à d'autres sujets.
Keywords: ADISQ; Anglophone press; Céline Dion; Journalism

Il fut un temps où l'on se voyait beaucoup, suivi de Lettres africaines et de Tombeau de Suzanne Guité - Julien, Pauline (Lanctôt Éditeur, 1998)

Show Girls - Lam, Meilan (Office national du film du Canada, 1998)
Show Girls celebrates Montreal's swinging Black jazz scene from the 1920s to the 1960s, when the city was wide open. Three women who danced in the legendary Black clubs of the day - Rockhead's Paradise, The Terminal, Café St. Michel - share their unforgettable memories of life at the centre of one of the world's hottest jazz spots. From the Roaring Twenties, through the Second World War and on into the golden era of clubs in the fifties and sixities, Show Girls chronicles the lives of Bernice, Tina and Olga - mixing their memories with rarely seen footage of the era. Their stories are told against a backdrop of the fascinating social and political history that made Montreal a jazz and nightclub hotspot for decades. It is a story of song and dance, music and pride.

A Bosnian Sephardic Woman in Kahnewake, Quebec - Cohen, Judith R. (Canadian Woman Studies/Les cahiers de la femme, 1996)

Women's Roles in Judeo-Spanish Song Traditions - Cohen, Judith R.; Sacks, Maurie (Active Voices: Women in Jewish Culture, 1995)

The Composer's Voice: "What women can do" - Dalen, Brenda (Canadian University Music Review / Revue de musique des universités canadiennes, 1995)
In this interview, conducted on 18 August 1994, Violet Balestreri Archer revisits her past, recreating the experiences of her youth from the earliest days of her childhood in Como and Montreal to her graduation from Yale University in 1949 and sharing highly personal memories of her family, teachers, and friends. She recalls her first visit to Italy, her school years, her piano lessons, her early attempts at composition, her participation in the Montreal Women's Symphony, and her compositional studies with Douglas Clarke at McGill University, Béla Bartók in New York, and Paul Hindemith at Yale University. In listening to her story, we discover "who" she is and "how" she succeeded in establishing her compositional voice and in creating a space or "room" for herself in a profession traditionally dominated by men.

Sierra norteña: The influence of Latin music on the French-Canadian popular song and dance scene, especially as reflected in the career of Alys Robi and the pedagogy of Maurice Lacasse-Morenoff - Sévigny, Jean-Pierre (Productions Juke-box, 1994)

Expressive Modes in the Judeo-Spanish Wedding Song - Anahory-Librowicz, Oro (New Horizons in Sephardic Studies, 1993)

The Music of the Songs: Musical Transcriptions and Commentary of the Songs Discussed by Oro Anahory-Librowicz "Expressive Modes in the Judeo-Spanish Wedding Song" - Cohen, Judith R. (New Horizons in Sephardic Studies, 1993)

Women and Judeo-Spanish Music - Cohen, Judith R. (Bridge, 1993)

Le couple Maubourg-Roberval : un apport décisif à l’implantation de l’art lyrique à Montréal - Paul, Hélène (L'Annuaire théâtral. Revue québécoise d’études théâtrales, 1993)
Un article de la revue L'Annuaire théâtral, diffusée par la plateforme Érudit.

Die Komponistin Violet Archer unter Berücksichtigung ihrer nationalen und internationalen Stellung im Musikleben [La compositrice Violet Archer au regard de sa position nationale et internationale dans la vie musicale] - Glathe, Kerstin (Université de Münster, 1992)

Alanis Obomsawin - Kivi, K. Linda (Canadian Women Making Music, 1992)

Pauline Julien - Kivi, K. Linda (Canadian Women Making Music, 1992)

La question de l'identité dans l'écriture de Pauline Julien - Rheault, Michel (Université du Québec à Montréal, 1991)

The Odyssey of Dahlia Obadia: Morocco, Israel, Canada - Sawa, Suzanne Myers (Canadian Folk Music Journal, 1991)
Dahlia Obadia interprète les danses de la tradition du moyen orient. Pendant sa carrières, elle a rémarque qu’il existe des grandes différences entre les interprétations de cette tradition vue de l’intérier et de l’extérieur. L’auteur décrit la vie de Dahlia et explore les problèmes qu’elle a affrontes pendant sa quête de sa propre identité culturelle.